Disposition of flavonoids via recycling: Direct biliary excretion of enterically or extrahepatically derived flavonoid glucuronides. Issue 5 (13th April 2016) - Zeng, Min; Sun, Rongjin; Basu, Sumit; Ma, Yong; Ge, Shufan; Yin, Taijun; Gao, Song; Zhang, Jun; Hu, Ming
Abstract : The present study is focused on understanding the roles played by intestine and liver in the disposition of flavonoids using intestinal and portal vein perfusion. We found that flavonoid aglycones were rapidly metabolized in the intestine and that the flavonoid glucuronides were then rapidly taken up by the hepatocytes and excreted into the bile. Since conjugates are rapidly hydrolyzed by microbes for absorption again, the novel finding is that enterohepatic recycling can occur without hepatic enzymes, which provides a new insight into the enterohepatic recycling process. Abstract : Scope: Enterohepatic recycling is often thought to involve mostly phase II metabolites generated in the liver. This study aims to determine if direct biliary excretion of extrahepatically generated glucuronides would also enable recycling. Methods and results: Conventional and modified intestinal perfusion models along with intestinal and liver microsomes were used to determine the contribution of extrahepatically derived glucuronides. Glucuronidation of four flavonoids (genistein, biochanin A, apigenin, and chrysin at 2.5–20 μM) were generally more rapid in the hepatic than intestinal microsomes. Furthermore, when aglycones (at 10 μM each) were perfused, larger (1.7–9 fold) amounts of glucuronides were found in the bile than in the luminal perfusate. However, higher concentrations of glucuronides were not found in jugular vein than portal vein, and apigenin glucuronide actually displayed a significantly lower concentration in jugular vein (<1 nM) than portal vein (≈4 nM). A direct portal infusion of four flavonoid glucuronides (5.9–10.4 μM perfused at 2 mL/h) showed that the vast majority (>65%) of the glucuronides (except for biochanin A glucuronide) administered were efficiently excreted into the bile. Conclusion: Direct biliary excretion of extrahepatically generated flavonoid glucuronides is a highly efficient clearance mechanism, which should enable enterohepatic recycling of flavonoids without hepatic conjugating enzymes.